Exploring of Technology and Engineering Literacy (TEL): What, Why, and How - Hamka, Defrizal; Riandi, Riandi; Rahma Suwarna, Irma (KnE Social Sciences, 2024)
Challenges in the 21st century that we face as a society certainly need to be handled by young people, in the end giving birth to an idea called Technology and Engineering Literacy (TEL). However, many people do not understand what, why, and how TEL. Therefore, this article discusses issues that are clearly of concern and related to what TEL is, why TEL should exist, and how TEL assessment is implemented in education, especially in science education. This research is included in the parameters of the theme content analysis. This research-based paper uses reflections on literature from various journals, articles, and other textbooks. TEL is the ability to develop solutions to solve problems, understand the principles and technological strategies needed to achieve goals, and use, understand, and evaluate technology. The three areas of TEL that NAEP will evaluate are technology and society, design and systems, and ICT. TEL is very important to be trained and improved in science learning as a provision for students to face 21st century education. The TEL assessment is a computer-based test, the items are composed of scenario-based assessment and discrete item sets, and the data is provided with longitudinal analysis. Implementation of TEL in Science Instruction can be done using learning methods that involve science, technology and engineering principles. Keywords: Exploring, TEL, What, Why, and How